The Labor Motivation of Rural Women in Newly Developed Urban Satellites: The Case of Izmir, Turkey - Kural, Melis (Journal of Regional and City Planning, 2019)
While urban developers plan to mobilize residents by reinforcing middle-class values, including settling them into urban satellites and offering career development courses, residents feel pleased with the housing opportunities but do not express interest in career advancement courses. From fieldwork observations and in-depth interviews with 35 female residents in a low-income urban satellite neighborhood (Zubeyde Hanim) in Izmir, Turkey, and by focusing on residents’ reactions to career development courses, in this study the residents’ experiences, connections, and desires in the urban renewal process were interpreted. It is argued that the aims of the urban renewal projects were not aligned with the residents’ needs. It was found that urban relocation is a communal process. If the official communication between authorities and the resettled population are designed in such a way that the daily life struggles and needs of the targeted population are taken into account, then the urban renewal programs can be designed and implemented more effectively. Abstrak. Sementara pengembang perkotaan berencana untuk memobilisasi penduduk dengan memperkuat nilai-nilai kelas menengah termasuk memukimkan mereka di kota-kota satelit dan menawarkan kursus pengembangan karir Warga merasa senang dengan peluang perumahan tersebut, tetapi tidak mengekspresikan minat dalam program pengembangan karir. Dari pengamatan lapangan dan wawancara mendalam dengan 35 penduduk perempuan di lingkungan kota satelit berpenghasilan rendah (Zubeyde Hanim) di Izmir, Turki, dan dengan berfokus pada reaksi penduduk terhadap kursus pengembangan karir, dilakukan penafsiran pengalaman, koneksi, dan keinginan dalam proses pembaruan perkotaan. Ditemukan tujuan proyek pembaruan perkotaan tidak selaras dengan kebutuhan warga. Relokasi kota adalah proses komunal. Namun, jika komunikasi resmi antara pihak berwenang dan penduduk yang dimukimkan ulang dirancang sedemikian rupa sehingga perjuangan kehidupan sehari-hari dan kebutuhan populasi yang ditargetkan diperhitungkan maka program pembaruan perkotaan dapat dirancang dan dilaksanakan dengan lebih efektif.Kata Kunci. pembaruan perkotaan, perumahan umum, wanita dan mobilitas sosial, Turki.